2017
DOI: 10.1016/j.gdata.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals common differential and global gene expression profiles in bluetongue virus serotype 16 (BTV-16) infected peripheral blood mononuclear cells (PBMCs) in sheep and goats

Abstract: Bluetongue is an economically important infectious, arthropod borne viral disease of domestic and wild ruminants, caused by Bluetongue virus (BTV). Sheep are considered the most susceptible hosts, while cattle, buffalo and goats serve as reservoirs. The viral pathogenesis of BTV resulting in presence or absence of clinical disease among different hosts is not clearly understood. In the present study, transcriptome of sheep and goats peripheral blood mononuclear cells infected with BTV-16 was explored. The diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 48 publications
5
24
1
Order By: Relevance
“…In the study of Li et al [4], various differentially expressed genes (DEGs) related to goat immune response, including inflammation, defense response, cell locomotion, and cytokine/chemokine-mediated signaling were revealed by transcriptome analysis with samples from BVDV2 artificially infected goat peripheral blood mononuclear cells (PBMCs). Similar methodology was done in the study of Singh et al [14], where various significant DEGs related to the immune system processes of goat and sheep against bluetongue virus serotype 16 (BTV-16) were revealed, such as NFκB, MAPK, Ras, NOD, RIG, TNF, TLR, JAK-STAT, and VEGF signaling pathways. Meanwhile, comparative transcriptomic analyses between infected and non-infected animals were conducted by Barreto et al [15], where infected bovine were observed to have massive changes in the expression profiles of keratinocyte, immune system, cell proliferation, and apoptosis genes.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the study of Li et al [4], various differentially expressed genes (DEGs) related to goat immune response, including inflammation, defense response, cell locomotion, and cytokine/chemokine-mediated signaling were revealed by transcriptome analysis with samples from BVDV2 artificially infected goat peripheral blood mononuclear cells (PBMCs). Similar methodology was done in the study of Singh et al [14], where various significant DEGs related to the immune system processes of goat and sheep against bluetongue virus serotype 16 (BTV-16) were revealed, such as NFκB, MAPK, Ras, NOD, RIG, TNF, TLR, JAK-STAT, and VEGF signaling pathways. Meanwhile, comparative transcriptomic analyses between infected and non-infected animals were conducted by Barreto et al [15], where infected bovine were observed to have massive changes in the expression profiles of keratinocyte, immune system, cell proliferation, and apoptosis genes.…”
Section: Introductionmentioning
confidence: 77%
“…Compared to DNA microarray-based technology, RNA-Seq provide greater dynamic range by directly revealing sequence identity crucial for annotation quantification of unknown genes and novel transcript isoforms [25,26]. In studies by Li et al, Singh et al, and Barreto et al [4,14,15], RNA-Seq based transcriptome analyses were used to successfully identify both up-and down-regulated genes related to the host immune response during BVDV, bluetongue virus of sheep and goats, and bovine papillomatosis infection, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs were the main target of BVDV infection, infection of lymphocytes and monocytes by BVDV resulted in lymphoid depletion of B cells, T helper cells, cytotoxic T cells and γ-δ T cells [20, 21]. PBMCs have been proved to be a suitable model for characterizing the host immune responses to virus infection and have been utilized for the evaluation of immune responses to animal viruses [17, 22, 23]. Global transcriptome analysis has been employed to explore the molecular events of host interaction with BVDV in bovine originated cells [2427].…”
Section: Introductionmentioning
confidence: 99%
“… For identified immune‐related pathways, genes were selected including ACTB (beta‐actin), H3F3A (H3‐histone family), PPIA (peptidylprolyl isomerase A), IRF3 (interferon regulatory factor 3), STAT2 (signal transducer and activator of transcription 2), HERC3 (Hect domain and RLD 3; protein‐coding gene), IFIT3 antibody (interferon‐induced protein with tetratricopeptide repeats 3; protein‐coding gene) (Puech et al, ; Singh et al, ). …”
Section: Resultsmentioning
confidence: 99%
“…Quantitative real‐time PCR of immune‐related and lipogenic gene expressions was carried out using the methods described by Puech, Dedieu, Chantal, and Rodrigues (), Singh et al () and Bahnamiri, Zali, Ganjkhanlou, Sadeghi, and Shahrbabak (). The beta‐actin gene ACTB (housekeeping gene) was used as an endogenous control for normalization of target gene(s) of interest.…”
Section: Methodsmentioning
confidence: 99%